2012
DOI: 10.1089/thy.2011.0185
|View full text |Cite
|
Sign up to set email alerts
|

Core-Needle Biopsy Is More Useful Than Repeat Fine-Needle Aspiration in Thyroid Nodules Read as Nondiagnostic or Atypia of Undetermined Significance by the Bethesda System for Reporting Thyroid Cytopathology

Abstract: After patients have had one FNA of a thyroid nodule yielding inconclusive diagnostic results (nondiagnostic or AUS/FLUS), CNB is more useful than rFNA for reducing the frequency of inconclusive diagnostic results. CNB will improve the diagnostic performance for malignancy more than rFNA in thyroid nodules that on the first FNA had nondiagnostic or AUS/FLUS readings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
315
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(338 citation statements)
references
References 25 publications
20
315
2
1
Order By: Relevance
“…[7][8][9]19 These studies reported that the rate of inconclusive CNB results ranged between 0% and 26%. Recently, Hahn et al 5 demonstrated that US-CNB is beneficial for the diagnosis of thyroid nodules with inconclusive US-guided FNA results.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]19 These studies reported that the rate of inconclusive CNB results ranged between 0% and 26%. Recently, Hahn et al 5 demonstrated that US-CNB is beneficial for the diagnosis of thyroid nodules with inconclusive US-guided FNA results.…”
Section: Discussionmentioning
confidence: 99%
“…Because US-guided CNB using a spring-activated biopsy needle has been reported safe and effective by Quinn et al, 23 several investigators have demonstrated the usefulness of CNB in diagnosing thyroid nodules with 90.3% (range, 78.5%-100%) sensitivity and 98.4% (range, 87%-100%) positive predictive value for thyroid malignancy. [18][19][20][24][25][26] Currently, the role of CNB has focused on the diagnosis of nodules with previously nondiagnostic results on FNA and, therefore, on preventing unnecessary diagnostic surgery. 19,24,25,27 For the diagnosis of a specific type of malignancy, however, CNB has also showed the possibility of superior diagnostic performance to that of FNA for thyroid lymphoma, anaplastic carcinoma, and metastasis in a small series of studies.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][24][25][26] Currently, the role of CNB has focused on the diagnosis of nodules with previously nondiagnostic results on FNA and, therefore, on preventing unnecessary diagnostic surgery. 19,24,25,27 For the diagnosis of a specific type of malignancy, however, CNB has also showed the possibility of superior diagnostic performance to that of FNA for thyroid lymphoma, anaplastic carcinoma, and metastasis in a small series of studies. 26,[28][29][30][31] The complication rate was reported to be Ͻ1% and was considered to be similar to that of FNA if an experienced clinician performed the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies (28,31) [but not all (30,32)] suggest that the ROM in a benign FNA after an initial AUS/FLUS biopsy is of intermediate risk between the two categories (i.e. the second benign FNA cannot make the first AUS/FLUS FNA go away).…”
Section: Current Management Of Cytologically Benign Thyroid Fna Biopsiesmentioning
confidence: 99%